Study of the Interaction Between Common Carp (Cyprinus carpio) and Silver Crucian Carp (Carassius auratus gibelio Bloch) - Bársony, Péter; Pócsi, László; Szabó, András (Acta Agraria Debreceniensis, 2005)
Some of the main questions in the fish farming are the good manuring and the success of the feeding. For the best result is very important that only those fishes take place in the fishponds what we want. It seems to be easy but difficult to do. One of the main challenges of the successful fish production in fishponds, is to rid ponds of the silver crucian carp. In the course of the experiment, carp fry were stocked in 5 nursing ponds at the same stocking rate, with different (0-, 50-, 100-, 150-, 200%) stocking rates of silver crucian carp fry, respectively. During the rearing season, weekly test fishings were made to control the growth of the fishes. At the end of the experiment, the yield/hectar and the growth rates were calculated. The experiment proved that the presence of the silver crucian carp in the fishponds causes lower growth rates and productivity in common carp. In the control pond (without silver crucian carp), the average weight of the common carp was 25 g and the yield/hectar was over 900 kg, while in the pond with the most silver crucian carp, the average weight of the common carp was 9 g and the yield/hectar was only 158 kg.